Russian Blockhouse in Alaska - Washington State University Vancouver Library; http://library.vancouver.wsu.edu/
An octagonal wooden structure with a cannon visible inside an octagonal opening in the side. This is the Russian block house in St. Michael, Alaska, built in the 1830s. 3.5 x 4.5 in.